The 'Dance' of Kinship Care in England and Ireland: Navigating a course between regulation and relationships - GILLIGAN, ROBERT (My University, 2013)
There has been a significant growth in the use of formal kinship care in the UK and Ireland in the last 20 years. The paper charts some of the reasons for the ‘organic growth’ of kinship care and the multiple dynamics that have shaped this. It shows that kinship care has grown relatively slowly in the more regulated care system of England, compared to the less regulated system in Ireland. Examination of these different trajectories suggests that: where the tendency to regulation is strong the choices of individual family members may also have an impact in response to state provision; cultural differences in the importance of family ties may play a part in decision-making processes; and that variations in levels of regulation and support may impact on the profile of the care system. It also serves to highlight that relationships may be the glue that brings formal kinship placements together and they may also be the glue that holds them together. Regulation (and how it is interpreted on the ground) can influence the climate of choices of the carer to start or keep going, but it cannot determine those choices. Clearly, regulation is required, but it seems wise not to see regulation as all-conquering in terms of influence. ‘Culture’ in a range of senses seems also to play a part. Further comparative study may reveal more about this ‘dance’ of kinship care and its balancing of regulatory and ‘cultural’ factors.
PUBLISHED
Keywords: kinship care; Foster care; Social work regulation; Looked after children; Out-of-home care; Cross-national comparison; Inclusive Society